The economics of transnational commons (Oxford, 1997)
The book draws together eminent contributors from fields as diverse as law, population studies, social anthropology, biologial sciences, and economics, to present authoritative accounts that combine empirical case-studies with rigorou theoretical foundations. Despite the multi-displinary approach, the main focus of the articles is the same; that the reciprocal externalities and problems of free-riding created by any common resource are complicated in the case of tranational commons by difficulties in monitoring, enforcement, and unequal access to information. Often using theories of negatiation taken from game theory, the studies then suggest possible solutions, both at an institutional and educational level.
Keywords: economic development projects